استخدامات منهج تحليل المضمون في بحوث الإعلام والاتصال بين التحليل الكمي والكيفي - جلولى, مختار (جامعة الوادي - University of Eloued, 2022)
يعد منهج تحليل المضمون واحد من المناهج التحليلية التي زاد إقبال الباحثين عليها في الدراسات الإعلامية والاتصالية لعدة اعتبارات لعل أبرزها القيمة العلمية التي أصبحت تحملها هذه البحوث من جهة وموضوعية الباحث من جهة أخرى، بالإضافة إلى جمعه بين التحليل الكمي القائم على الأرقام والبيانات والتحليل الكيفي الذي يبحث في دلالة هذه الأرقام والخلفية المروج لها. وإذا كان التوجه الأول السائد في البداية يركز على التحليل الكمي أكثر واعتبار تحليل المضمون منهجا وأسلوبا كميا بامتياز، على اعتبار أنه يعتمد العد والقياس والتكرار في رصد الفئات، فإن التوجه الجديد يزاوج بين التحليلين الكمي والكيفي ويعتبر التحليل الكمي رصد لأرقام وبيانات لا قيمة لها ما لم تتوج بالتحليل والتفسير الكيفي الذي يعطيها دلالاتها الحقيقية. Abstract: The content analysis approach is one of the analytical approaches that have increased the demand of researchers in media and communication studies for several considerations, perhaps the most prominent of which is the scientific value that these researches have become on the one hand and the objectivity of the researcher on the other hand, in addition to its combination of quantitative analysis based on numbers and data and qualitative analysis that investigates In the connotation of these figures and the promoter background. And if the prevailing first orientation in the beginning focuses on quantitative analysis more and considers content analysis an excellent quantitative approach and method, given that it relies on counting, measurement and repetition in monitoring categories, then the new approach combines quantitative and qualitative analysis, and quantitative analysis is a monitoring of numbers and data that have no value unless It culminates in qualitative analysis and interpretation that gives it its true significance.
مقال
Keywords: استخدامات ؛ تحليل مضمون ؛ تحليل كمي ؛ تحليل كيفي؛ بحوث الإعلام; uses; content analysis; quantitative analysis; qualitative analysis; Media Research